(untitled) (Fiep Bulletin - online, 2016)
The objective of this research is to present the importance of play chess in Physical Education for Elementary l having specific objectives present a brief history of the game of chess; emphasize the benefits of chess in the school environment and present a pedagogical possibility for teaching chess in elementary I. The methodology used was to field research exploratory, where a questionnaire was used to obtain the information. The study sought to understand whether chess is being used in an educational way in Physical Education classes and found that this missing property on this specific knowledge on the part of teachers to teach that content within the Physical Education classes.